Cyborg Theatre - Parker-Starbuck, J. author. aut Link
XV, 241 p.
Keywords: This book articulates the first theoretical context for a 'cyborg theatre', metaphorically integrating on-stage bodies with the technologized, digitized, or mediatized, to re-imagine subjectivity for a post-human age. It covers a variety of examples, to propose new theoretical tools for understanding performance in our changing world.